Association of stress with nutrition literacy, eating behavior, and physical activity: A cross-sectional study of university students in Bangladesh. - Towhid Hasan; Nibadita Majumder; Marjia Sultana; Md Mahmudul Hasan Shohag; Nishat Subah Tithi (PLoS ONE, 2025)
Background Increased levels of stress among university students have an effect on their physical and mental well-being and may lower their learning outcomes and overall satisfaction. While lifestyle factors like nutrition literacy, eating behavior, and physical activity are known to influence stress, their combined association has not been explored among university students in Bangladesh. Objectives This study intended to identify the level of perceived stress among university students in Bangladesh and explore its relationship with their nutrition literacy, healthy eating behavior, and physical activity. Methods This cross-sectional study was conducted from May to June 2024 among 450 students of Noakhali Science and Technology University, Bangladesh. Data were collected through a structured questionnaire assessing socio-demographic characteristics, perceived stress (perceived stress scale [PSS]), nutrition literacy (nutrition literacy scale [NLS]), healthy eating behavior (healthy eating behavior scale [HEBS]) and physical activity (international physical activity questionnaire - short form [IPAQ-SF]). Results Results indicated a moderate level of perceived stress among students, having a mean PSS score of 19.88 ± 4.67 out of 40 points. About half of the students had low nutrition literacy (57.3%) and poor healthy eating behavior (47.6%); however, almost all did sufficient physical activity (97.3%). Adjusted linear regression analysis revealed a significant negative association of perceived stress with nutrition literacy (β = -0.130, 95% confidence interval [CI]: -0.186, -0.092; P = 0.006) and healthy eating behavior (β = -0.139, 95% CI: -0.232, -0.028; P = 0.003) among university students. However, physical activity was not significantly associated with their perceived stress level (β = -0.039, 95% CI: -0.088, 0.010; P = 0.395). Conclusion The present findings suggested that nutrition literacy and healthy eating behavior significantly impact perceived stress among university students, highlighting an urgent need for holistic health intervention in academic settings.